Generation of the ICGi019-B-1 and ICGi019-B-2 lines via correction of the p.Met659Ile (c.1977G>A) variant in MYH7 of patient-specific induced pluripotent stem cells using CRISPR/Cas9 - A. E. Shulgina; S. V. Pavlova; J. M. Minina; S. M. Zakian; E. V. Dementyeva (Вавиловский журнал генетики и селекции, 2025)
The problem of interpretation of the genetic data from patients with inherited cardiovascular diseases still remains relevant. To date, the clinical significance of approximately 40 % of variants in genes associated with in herited cardiovascular diseases is uncertain, which requires new approaches to the assessment of their pathogenetic contribution. A combination of the induced pluripotent stem cell (iPSC) technology and editing the iPSC genome with CRISPR/Cas9 is thought to be the most promising tool for clarifying variant pathogenicity. A variant of unknown significance in MYH7, p.Met659Ile (c.1977G>A), was previously identified in several genetic screenings of hypertrophic cardiomyopathy patients. In this study, the single nucleotide substitution was corrected with CRISPR/Cas9 in iPSCs generated from a carrier of the variant. As a result, two iPSC lines (ICGi019-B-1 and ICGi019-B-2) were generated and characterized using a standard set of methods. The iPSC lines with the corrected p.Met659Ile (c.1977G>A) variant in MYH7 possessed a morphology characteristic of human pluripotent cells, expressed markers of the pluripotent state (the OCT4, SOX2, NANOG transcription factors and SSEA-4 surface antigen), were able to give rise to derivatives of three germ layers during spontaneous differentiation, and retained a normal karyotype (46,XY). No CRISPR/Cas9 off-target activity was found in the ICGi019-B-1 and ICGi019-B-2 iPSC lines. The maintenance of the pluripotent state and normal karyotype and the absence of CRISPR/Cas9 off-target activity in the iPSC lines with the corrected p.Met659Ile (c.1977G>A) variant in MYH7 allow using the iPSC lines as an isogenic control for further studies of the variant pathogenicity and its impact on the hypertrophic cardiomyopathy development.